Analisis Tingkat Inflasi Selama Pandemi Covid 19 Terkonfirmasi di Negara Mayoritas Muslim - Desty Prinatasya (ITB AAS INDONESIA Surakarta, 2023)
Inflation can come at any time and cannot be controlled with the Covid-19 pandemic confirmed In muslim majaraty countries to add shocks to the inflation level, so the problem is to examine the price reduction in consumers, export value, consumer exchange rate and confirmed covid-19 confirmed inflation level. The study was conducted in 2020 from March to September using secondary data with analysis using multiple linear regression. Based on the results of the analysis, it was found that the level of inflation is positively patterned simultaneously from export value, consumer price and export value. Meanwhile, the export value and consumer exchange rate are partially patterned positively and have a very real effect on the inflantion rate. But it has no real effect on consumer prices and covid 19 is confirmed at the inflantion rate. Keywords: Consumer price level index, export value, exchange rate, confirmed Covid-19, and inflation rate